Hibridity and Cutural Identity Through Jude as a Syrian character in Warga’s Novel Other Words For Home - Arief Rahman Hakim; Siti Deviana Rahma Nurhusna (Vivid: Journal of Language and Literature, 2022)
This research aims to show how Jude, as a Syrian character in Other Words For Home, interprets the notion of a home and how it explicitly opposes American Exceptionalism. The writer chooses the study of home in the novel to enhance the analysis of Other Words for Home, which generally focuses on the novel's Syrian character. This research uses postcolonial diasporic criticism especially hybridity and cultural identity as the concept in Other Words for Home. The home is not only a place of immigrants for the diaspora but is related geographically and psychologically. For diasporas, the home has become a wounded concept that forces them to deal with scars, blisters and sores, and psychic traumas while on the move. Warga tells the story of Syrian immigrants who moved to America due to the political turmoil in Syria. She portrays racism, alienation, and prejudice as a black spectacle in which Jude becomes a victim. Jude is depicted as a teenager struggling to acculturate herself in in-between spaces between homeland and hostland. It creates a hybrid identity. Jude's hybrid identity is manifested by her use of mixed dialects in daily conversation, behavior, and triumph. This study demonstrates that identity is a fluid concept. Furthermore, through this hybrid identity Jude challenges the dominance of American Exceptionalism in the US and in the world regarding Arab Muslims.